Intraday lead-lag relationship between warrants and futures contracts - Akçalı, Deniz (İstanbul Bilgi Üniversitesi, 2012)
The aim of this thesis is to investigate empirically the intraday lead-lag relationship between warrants and futures market as applied to those traded at the Istanbul Stock Exchange (ISE) and Turkish Derivatives Exchange (Turkdex). Focus is used an intuitive method to examine the intraday lead-lag relation, if any, in the high frequency intraday data of warrants and futures which have same underlying stocks index using parametric and nonparametric methods at 5-minutes regular time interval. The data set for the study consists of the 5 minutes time interval closing values of the ISE 30 index futures traded at the Turkdex and ISE 30 index put and call warrants traded at ISE and issued by Deutsche Bank, which are considered from January 6, 2012 to February 29, 2012 period; from May 8, 2012 to June 29, 2012 period and from July 2, 2012 to August 31, 2012 for near month futures contracts, near month and mostly heavily traded put and call warrants. As parametric methods, cross correlation functions and Granger causality model are used to investigate whether a short term relationship among the time exists or not and vector autoregressive model is used to examine the short-term relationship between future contracts and warrants. Impulse-response functions and variance decomposition methods are also used as complementary methods to show the effects of the change in the error terms of the variables in the study on the other variables. Counting method is used as non-parametric method and statistically significance of its results is tested by chi-square method. We find that both parametric method's and non-parametric counting method's results shows that there is an evidence that futures contract market lead the warrant markets in Turkey. On the contrary, warrants do not lead futures market. This result is statistically significant.

Bu çalışmanın amacı, dayanak varlığı İMKB-30 hisse senedi endeksi olan, İMKB’de işlem gören varant ve VOB’da işlem gören futures sözleşmeleri arasındaki gün içi öncül-ardıl ilişkisini araştırmaktır. Çalışmada, aynı dayanak varlığa sahip varant ve vadeli işlem sözleşmeleri arasındaki öncül-ardıl ilişkisinin 5’er dakikalık zaman aralıklarıyla temin edilen kotasyon verileri ile incelenmesine odaklanılmıştır. Çalışmada, 06.01.2012-29.02.2012, 08.05.2012 ve 02.07.2012-31.08.2012 tarihleri için İMKB-30 endeksine dayalı vadeli işlem sözleşmeleri ile alım satım varantlarının kapanış fiyatları kullanılmış, en çok işlem gören varantlar ile varantların vadesine yakın vade sonu olan futures sözleşmeler seçilmiştir. Parametrik yöntemler kapsamında, çapraz korelasyon ve Granger Nedensellik Testleri ile Vektör Otoregresyon Modeli ile varantlar ve futures sözleşmeler arasındaki kısa dönemli ilişki analiz edilmiştir. Etki tepki fonksiyonları ile varyans ayrıştırma metotları uygulanmış ve hata terimindeki değişimler analiz edilmiştir. Parametrik olmayan sayma metodu uygulanmış, istatistiksel anlamlılığı Ki-Kare Testi ile ölçülmüştür. Gerek parametrik gerekse parametrik olmayan yöntemlerin sonuçları, Türkiye’de futures sözleşmelerin işlem gördüğü piyasaların varant piyasasına öncülük ettiği yönünde bulgular sunmuştur. Diğer yandan, varant piyasasına öncülük ettiği yönünde bir kanıta rastlanmamıştır. Elde edilen sonuçlar istatistiksel olarak anlamlı bulunmuştur
Varant ve futures sözleşmeleri arasındaki gün içi öncül-ardıl İlişkisi: İmkb 30 endeksi üzerine bir çalışma